A relaxor ferroelectric polymer with an ultrahigh dielectric constant largely promotes the dissociation of lithium salts to achieve high ionic conductivity. Issue 11 (20th October 2021) - Huang, Yan-Fei; Gu, Tian; Rui, Guanchun; Shi, Peiran; Fu, Wenbo; Chen, Lai; Liu, Xiaotong; Zeng, Jianping; Kang, Benhao; Yan, Zhichao; Stadler, Florian J.; Zhu, Lei; et al.
Abstract : A unique relaxor ferroelectric P(VDF-TrFE-CTFE) is investigated as a matrix of SPEs. The P(VDF-TrFE-CTFE) with ultrahigh ε r promotes the dissociation of LiTFSI to greatly enhance the ionic conductivity and the transference number of lithium ions. Abstract : The extremely low room-temperature ionic conductivity of solid-state polymer electrolytes (SPEs) ranging from 10 −7 to 10 −5 S cm −1 seriously restricts their practical application in solid-state lithium metal batteries (LMBs). Herein, a unique relaxor ferroelectric (RFE) polymer of poly(vinylidene fluoride- co -trifluoroethylene- co -chlorotrifluoroethylene) [P(VDF-TrFE-CTFE)] is first investigated as a matrix of SPEs. We find that the P(VDF-TrFE-CTFE) with an ultrahigh dielectric constant ( ε r ) of 44 presents a stronger solvation ability towards lithium ions, which promotes the dissociation of LiN(SO2 CF3 )2 to form more free charge carriers and enhances their mobility compared to the conventional PVDF with a low ε r of 9. The P(VDF-TrFE-CTFE) based SPEs show a much higher ionic conductivity of 3.10 × 10 −4 S cm −1 at 25 °C and lower activation energy (0.26 eV) than PVDF based SPEs (1.77 × 10 −5 S cm −1 and 0.49 eV). The PVDF blended with the P(VDF-TrFE-CTFE) or dielectric fillers such as BaTiO3 further confirm that the hybrid electrolytes with a larger ε r show a higher ionic conductivity. In addition, very tight interfaces of P(VDF-TrFE-CTFE) based SPEs with both the cathode and Li metal anode are constructed to ensure a stable interfacial resistance during cycling. The LiFePO4 /Li and LiNi0.8 Co0.1 Mo0.1 O2 /Li batteries using P(VDF-TrFE-CTFE) based SPEs present a stable cycling performance at 25 °C. This work proposes a new strategy and opens a new research area to construct SPEs with high ionic conductivity by greatly increasing the ε r of polymers.